Unnatural exposure - Cornwell, Patricia (Fiction, crime, 1997)
On the trail of a serial killer, Dr Kay Scarpetta follows the forensic footprints of a victim's life unconvinced that the murder is the work of the same killer. She begins to believe someone is on the point of releasing the smallpox virus back into a world which has destroyed all vaccine stocks.